2005
DOI: 10.1136/bjsm.2004.011627
|View full text |Cite
|
Sign up to set email alerts
|

Relation between foot arch index and ankle strength in elite gymnasts: a preliminary study

Abstract: Background: Gymnasts usually start intensive training from early childhood. The impact of such strenuous training on the musculoskeletal system is not clear. Objectives: To evaluate the relation between muscle strength of the ankle joint and foot structure in gymnasts. Methods: The study population comprised 20 high level male gymnasts and 17 non-athletic healthy male controls. Arch indices were measured using a podoscope. Ankle plantar/dorsiflexion and eversion/ inversion strengths were measured using a Biode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 5 publications
2
17
0
2
Order By: Relevance
“…Kulthanan, Techakampuch, and Bed (2004) and Aydog et al (2004) reported no statistically significant difference in foot posture between athletes and nonathletes based on two measurements including the flat index and sole arch index. In a further study, the same group of researchers showed that the sole arch index of gymnasts and handball players were significantly lower than those of non-athletic controls (Aydog, Tetik, Demirel, & Doral, 2005b). However, the sole arch index of wrestlers was significantly different from those of other athletes and higher than the non-athletic controls.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Kulthanan, Techakampuch, and Bed (2004) and Aydog et al (2004) reported no statistically significant difference in foot posture between athletes and nonathletes based on two measurements including the flat index and sole arch index. In a further study, the same group of researchers showed that the sole arch index of gymnasts and handball players were significantly lower than those of non-athletic controls (Aydog, Tetik, Demirel, & Doral, 2005b). However, the sole arch index of wrestlers was significantly different from those of other athletes and higher than the non-athletic controls.…”
Section: Introductionmentioning
confidence: 90%
“…However, with sufficient rest and recovery, repetitive mechanical loading can stimulate metabolism and increase strength of the ligaments. Similarly, certain muscles in the foot and ankle that have a lowering or elevating effect on the medial longitudinal arch can be strengthened or inhibited through sports participation and training (Aydog, et al, 2005a;Van Boerum & Sangeorzan, 2003). Further studies with other measurements such as muscle strength or joint range of motion are needed to explore possible mechanisms explaining the observed changes in foot posture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Za gad nie niem bu do wy i funk cji sto py zaj mu ją się spe cja li ści z wie lu dzie dzin na uki, od ana to mii, poprzez an tro po me trię, ra dio lo gię, or to pe dię, bio me chani kę, er go no mię, po fi zjo te ra pię i cha rak te ry zu ją zmiany roz wo jo we w spo sób spe cy ficz ny dla da nej dyscy pli ny na uki [1][2][3][4][5][6][7][8]. Prze gląd pu bli ka cji do ty czą cych dia gno sty ki stóp wska zu je na roz bie żno ści do ty czą -ce czę sto ści wy stę po wa nia pła sko sto pia, co zda niem au to rów po dyk to wa ne jest bra kiem norm dla stóp pra wi dło wych, nie zna jo mo ścią roz wo ju sto py w onto ge ne zie, ró żnym me to do lo gicz nym po dej ściem do ba dań, ale być mo że rów nież bra kiem da nych na te mat traf no ści do bo ru wskaź ni ków słu żą cych do oceny bu do wy sto py.…”
Section: Wstępunclassified